The Causes and Courses of Nonviolent and Violent Delinquency among South Korean Adolescents. Issue 7 (3rd July 2019) - Bax, Trent; Hlasny, Vladimir
ABSTRACT: This study combines and compares data from the Korean Youth Panel Survey and the Korean Children and Youth Panel Survey to examine the effects parenting, peers, school, social structure, and personality exert on nonviolent and violent delinquency among 5, 462 male and 5, 103 female adolescents in South Korea. Overall, parental effects were found to be more important than peer effects, but their influence diminishes relative to that of peer effects with age. The semiparametric group-based modeling approach identifies distinct groups of stable nondelinquents, stable moderates, moderate escalators, de-escalators, and desistors (but not chronic offenders). Lastly, this study does not provide support for a public discourse that infers juvenile delinquency has increased in frequency and severity.